2016
DOI: 10.1155/2016/4165750
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Physiological Plant Responses to Drought Stress inThymus citriodorus

Abstract: Water availability is considered as a determinant factor that affects plant growth. The commercial medicinal values of an aromatic plant rely on the presence of secondary metabolites that are affected under water shortage. Two-year-oldThymus citriodorusplants were subjected to different polyethylene glycol (PEG-6000) levels (0, 2%, and 4%) under greenhouse condition. PEG treatment lasted for 15 days. Thyme plant showed a morphological drought avoidance mechanism by maintaining the root system development throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
59
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(66 citation statements)
references
References 26 publications
6
59
1
Order By: Relevance
“…In rice, it was reported that rolled leaves transpire 41 per cent less water than did the unrolled ones [34] and then help genotypes to better sustain drought. More importantly, the drought resistant genotypes WC17, WC18 and WC14 increased the R/S ratio under drought which is an important indicator of drought avoidance [35]. This is achieved by maintaining the root system development through shoot weight reduction resulting in promoted root absorption.…”
Section: Drought Avoidance and Tolerance Are Required For Resistance mentioning
confidence: 99%
See 1 more Smart Citation
“…In rice, it was reported that rolled leaves transpire 41 per cent less water than did the unrolled ones [34] and then help genotypes to better sustain drought. More importantly, the drought resistant genotypes WC17, WC18 and WC14 increased the R/S ratio under drought which is an important indicator of drought avoidance [35]. This is achieved by maintaining the root system development through shoot weight reduction resulting in promoted root absorption.…”
Section: Drought Avoidance and Tolerance Are Required For Resistance mentioning
confidence: 99%
“…This is achieved by maintaining the root system development through shoot weight reduction resulting in promoted root absorption. Availability of water thus improves maintenance of cell turgor and support aboveground tissue growth during water stress [35].…”
Section: Drought Avoidance and Tolerance Are Required For Resistance mentioning
confidence: 99%
“…The stress occurs when soil water availability is reduced to critical levels that stop growth and normal functioning of plants (Ramakrishna and Ravishankar, 2011). In response to drought, however, plants can display a suite of physiological, biochemical, and morphological adjustments to diminish the negative impact of the stress on fitness (Potters et al, 2007;Atkinson and Urwin, 2012;Osakabe et al, 2013;Tátrai et al, 2016). Accumulating recent research suggests that these phenotypic adjustments that allow plants to face stressful situations may be positively modulated by symbiotic microorganisms (Dupont et al, 2015;Wani et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a complex multi-level regulatory network, controlling plant adaptive responses to drought stress, is required. Studies of such responses to water deficit such as stomata closure, expression of stress-specific genes, accumulation of osmolytes and up-regulation of antioxidant systems recently made considerable progress [17,35,36,37,38]. It was shown, that the mechanisms, underlying stress-resistance, are crucial for plant survival, and are associated with significant changes in the patterns of metabolites and proteins [10,15,35].…”
Section: Introductionmentioning
confidence: 99%